Answer:
(-3, 2.5)
Step-by-step explanation:
The midpoint of two points of coordinates (x1, y1) and (x2, y2) has the following coordinates
![((x_1+x_2)/(2),(y_1+y_2)/(2)_{})](https://img.qammunity.org/2023/formulas/mathematics/college/hk4kac2lef641lb1i7qdsldypshdgs9yto.png)
Then, the midpoint can be calculated replacing (x1, y1) = (3, 3) and (x2, y2) = (-9, 2), so
![((3+(-9))/(2),(3+2)/(2))=((-6)/(2),(5)/(2))=(-3,2.5)](https://img.qammunity.org/2023/formulas/mathematics/college/p47g1nldwlou906ooef1lgwsd04ldfa503.png)
Therefore, the midpoint is (-3, 2.5)